Wld(S) Prevents Axon Degeneration through Increased Mitochondrial Flux and Enhanced Mitochondrial Ca(2+) Buffering. - Avery, M.A.; Rooney, T.M.; Pandya, J.D.; Wishart, T.M.; Gillingwater, T.H.; Geddes, J.W.; Sullivan, P.G.; Freeman, M.R. (Current Biology, 2012)
Wld(S) (slow Wallerian degeneration) is a remarkable protein that can suppress Wallerian degeneration of axons and synapses, but how it exerts this effect remains unclear. Here, using Drosophila and mouse models, we identify mitochondria as a key site of action for Wld(S) neuroprotective function. Targeting the NAD(+) biosynthetic enzyme Nmnat to mitochondria was sufficient to fully phenocopy Wld(S), and Wld(S) was specifically localized to mitochondria in synaptic preparations from mouse brain. Axotomy of live wild-type axons induced a dramatic spike in axoplasmic Ca(2+) and termination of mitochondrial movement-Wld(S) potently suppressed both of these events. Surprisingly, Wld(S) also promoted increased basal mitochondrial motility in axons before injury, and genetically suppressing mitochondrial motility in vivo dramatically reduced the protective effect of Wld(S). Intriguingly, purified mitochondria from Wld(S) mice exhibited enhanced Ca(2+) buffering capacity. We propose that the enhanced Ca(2+) buffering capacity of Wld(S+) mitochondria leads to increased mitochondrial motility, suppression of axotomy-induced Ca(2+) elevation in axons, and thereby suppression of Wallerian degeneration.